Emerging role of astrocytes in oxytocin-mediated control of neural circuits and brain functions - Baudon, Angel; Creusot, Etienne Clauss; Althammer, Ferdinand; Schaaf, Christian P.; Charlet, Alexandre (Progress in neurobiology, 2022)
The neuropeptide oxytocin has been in the focus of scientists for decades due to its profound and pleiotropic effects on physiology, activity of neuronal circuits and behaviors, among which sociality. Until recently, it was believed that oxytocinergic action exclusively occurs through direct activation of neuronal oxytocin receptors. However, several studies demonstrated the existence and functional relevance of astroglial oxytocin receptors in various brain regions in the mouse and rat brain. Astrocytic signaling and activity is critical for many important physiological processes including metabolism, neurotransmitter clearance from the synaptic cleft and integrated brain functions. While it can be speculated that oxytocinergic action on astrocytes predominantly facilitates neuromodulation via the release of specific gliotransmitters, the precise role of astrocytic oxytocin receptors remains elusive. In this review, we discuss the latest studies on the interaction between the oxytocinergic system and astrocytes, including detailed information about intracellular cascades, and speculate about future research directions on astrocytic oxytocin signaling.
Online verfügbar am 21. Juli 2022, Artikelversion vom 26. Juli 2022
Gesehen am 05.09.2022